2020
DOI: 10.1093/abbs/gmaa011
|View full text |Cite
|
Sign up to set email alerts
|

Comparative phosphoproteomic analysis of compatible and incompatible pollination in L.

Abstract: Self-incompatibility (SI) promotes outbreeding and prevents self-fertilization to promote genetic diversity in angiosperms. Several studies have been carried to investigate SI signaling in plants; however, protein phosphorylation and dephosphorylation in the fine-tuning of the SI response remain insufficiently understood. Here, we performed a phosphoproteomic analysis to identify the phosphoproteins in the stigma of self-compatible ‘Westar’ and self-incompatible ‘W-3’ Brassica napus lines. A total of 4109 phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…A phosphoprotein, 14–3–3 was identified to have a potential role in seed development. Phosphoproteomics also established that β carbonic anhydrase 1 undergoes dephosphorylation at Tyr207 amino acid site during drought conditions in B. napus and helps the plant to adapt and sustain drought The work of Duan et al, in B. napus revealed that there were 405 and 248 phosphoproteins which showed differential abundance in self-incompatible and self-compatible pollination groups. The key proteins like MLPK, SRK, CML42, CDPK19, EIN2, ABF3, RPM1 interacting protein 4 and homologues of BKI and BZR1/BES1 showed differential phosphorylation in the two groups, indicating phosphorylation has a central role in controlling compatibility of pollen during pollen–pistil interaction.…”
Section: Post-translational Modifications In Brassicamentioning
confidence: 96%
“…A phosphoprotein, 14–3–3 was identified to have a potential role in seed development. Phosphoproteomics also established that β carbonic anhydrase 1 undergoes dephosphorylation at Tyr207 amino acid site during drought conditions in B. napus and helps the plant to adapt and sustain drought The work of Duan et al, in B. napus revealed that there were 405 and 248 phosphoproteins which showed differential abundance in self-incompatible and self-compatible pollination groups. The key proteins like MLPK, SRK, CML42, CDPK19, EIN2, ABF3, RPM1 interacting protein 4 and homologues of BKI and BZR1/BES1 showed differential phosphorylation in the two groups, indicating phosphorylation has a central role in controlling compatibility of pollen during pollen–pistil interaction.…”
Section: Post-translational Modifications In Brassicamentioning
confidence: 96%
“…In SSI, such as in Asteraceae and Convolvulaceae, the SI reaction was determined by two polymorphic S loci that were genetically linked: pollen-coat-specific cysteine-rich protein (SCR) and stigma-specific serine/threonine receptor kinase (SRK), which could inhibit the germination and growth of self-pollen ( Wang et al., 2014 ; Nasrallah, 2019 ). In GSI, such as in Solanaceae and Rosaceae, S-specificity was determined by haploid pollen ( Duan et al., 2020 ) and controlled by a single S-locus composed of two linked polymorphic genes: pollen-specific F-box protein (SFB/SLF) and style-specific T2 ribonuclease (S-RNase) ( Gordillo-Romero et al., 2020 ). Another GSI mechanism observed in Papaver rhoeas showed that incompatible pollen could trigger the interaction between the male S-loci PrpS and the female S-loci PrsS , which leads to Ca 2+ signaling cascades and initiates programmed cell death (PCD) ( Wheeler et al., 2009 ; Eaves et al., 2014 ; Bedinger et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, non-S locus gene disruption also changes the SI phenotypes, such as M-locus protein kinase (MLPK) [36,43,44] and ARC1 (Armadillo repeat-containing protein 1(ARC1) [45][46][47][48], which are the self-incompatible factors. With the development of molecular technology and sequencing strategy, transcriptomicse and proteomics have promoted SI signal pathway research [49][50][51]. Some genes, such as exocyst complex subunit A1(EXO70A1), Phospholipase D α1(PLDα1), and Glyoxalase1(GLO1), were identified as self-compatible factors working downstream of ARC1 [47,[52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%